Pengalaman Keluarga Selama Mendampingi Pasien di Intensif Care Unit: Scoping Review - Sutisna, Fitri Nur Megasari; Kosasih, Cecep Eli; Nur’aeni, Aan (Universitas Malahayati, 2025)
ABSTRACT Family members may experience a range of stressors while the patient is receiving treatment in the intensive care unit (ICU), including poor communication, doubts about the patient's survival or recovery, and a lack of support for collaborative decision-making. These stressors can cause feelings of helplessness and anxiety. Family support and presence are essential to the recovery of patients receiving intensive care unit treatment. In addition to the patient's recovery, the family will have a unique experience that may have an impact on their lives, which is why nursing care should be given with consideration. Investigating family experiences when accompanying critical patients in the intensive care unit. Using the inclusion criteria of publications 1) published between 2014 and 2024, a scoping review was conducted by gathering a variety of pertinent papers from electronic databases such PubMed, EBSCO Host, and Scopus. 2) in English 3) entire text accessible 4) talking about family experiences in the intensive care unit. An analysis was done on 10 research studies that were chosen to fit the requirements, and three key themes emerged: 1) anxiety disorders, 2) information needs, and 3) communication and interaction issues with ICU personnel. The primary psychological effect on family members of patients receiving intensive care unit treatment is anxiety. Lack of knowledge about the patient's health frequently causes this anxiety issue. It makes it impossible for the patient's family to fulfill their duty and function in making decisions for them. Poor communication and interaction issues between the patient's family and ICU staff can also contribute to this lack of information, so it is crucial for nurses to have interpersonal communication skills in order to ensure that all information is clearly understood by the family and can ultimately assist them in making decisions regarding the patient. Keywords: ICU, Information, Anxiety, Communication, Family Experience. ABSTRAK Selama proses perawatan pasien di ICU, anggota keluarga dapat terpapar pada berbagai pemicu stres, seperti masalah komunikasi, ketidakpastian mengenai kelangsungan hidup atau rehabilitasi pasien, dan kurangnya dukungan terhadap keputusan bersama, serta dapat menimbulkan perasaan cemas dan ketidakberdayaan. Kehadiran keluarga selama proses perawatan pasien di ICU ini bukan hanya berdampak terhadap proses penyembuhan pasien, tapi juga akan memberikan pengalaman tersendiri bagi keluarga yang dapat memberikan pengaruh tertentu bagi kehidupannya, sehingga hal ini patut menjadi perhatian dalam pemberian asuhan keperawatan. Menggali pengalaman keluarga selama mendampingi pasien kritis di unit rawat intensif. Scoping review dengan mengumpulkan berbagai artikel yang relevan dari database elektronik seperti PubMed, EBSCO host, dan Scopus. dengan kriteria inklusi artikel 1) terbit tahun 2014-2024 2) berbahasa Inggris 3) tersedia full text 4) membahas pengalaman keluarga dalam lingkup ICU dewasa. Analisis dilakukan terhadap Sepuluh artikel penelitian yang dinilai memenuhi syarat dan ditemukan tiga tema utama, yaitu : yaitu 1) gangguan kecemasan, 2) kebutuhan akan informasi, 3) gangguan komunikasi dan interaksi dengan staf ICU. Kecemasan menjadi dampak psikologis utama yang dialami oleh anggota keluarga dari pasien ICU, dan seringkali dipicu oleh kurangnya informasi yang berkaitan dengan kondisi pasien. yang mengakibatkan keluarga tidak dapat menjalankan peran dan fungsinya dalam pengambilan keputusan bagi pasien. Kurangnya informasi ini juga dapat disebabkan oleh masalah komunikasi dan interaksi yang buruk antara keluarga pasien dengan staf ICU, sehingga penting sekali bagi perawat untuk memiliki kemampuan interpersonal dalam berkomunikasi, agar segala informasi dapat tersampaikan dan dipahami dengan baik oleh keluarga, yang pada akhirnya dapat membantu keluarga dalam pengambilan keputusan bagi pasien. Kata Kunci: ICU, Informasi, Kecemasan, Komunikasi, Pengalaman Keluarga.